ECONOMIC AND ECOLOGICAL FEATURES OF THE FORMATION OF AGRICULTURAL LAND USE IN TERMS OF NEW LAND RELATIONS - Druhak, V. M. (Land Management, Cadastre and Land Monitoring, 2013)
Proved economic and environmental features of the formation of new land as an object of property and land relations in modern terms, hence the development of new methodological approaches to land management .